All roads lead to the motor cortex: psychomotor mechanisms and their biochemical modulation in psychiatric disorders - Northoff, Georg; Hirjak, Dusan; Wolf, Robert Christian; Magioncalda, Paola; Martino, Matteo (Molecular psychiatry, 2021)
Psychomotor abnormalities have been abundantly observed in psychiatric disorders like major depressive disorder (MDD), bipolar disorder (BD), and schizophrenia (SCH). Although early psychopathological descriptions highlighted the truly psychomotor nature of these abnormalities, more recent investigations conceive them rather in purely motor terms. This has led to an emphasis of dopamine-based abnormalities in subcortical-cortical circuits including substantia nigra, basal ganglia, thalamus, and motor cortex. Following recent findings in MDD, BD, and SCH, we suggest a concept of psychomotor symptoms in the literal sense of the term by highlighting three specifically psychomotor (rather than motor) mechanisms including their biochemical modulation. These include: (i) modulation of dopamine- and substantia nigra-based subcortical-cortical motor circuit by primarily non-motor subcortical raphe nucleus and serotonin via basal ganglia and thalamus (as well as by other neurotransmitters like glutamate and GABA); (ii) modulation of motor cortex and motor network by non-motor cortical networks like default-mode network and sensory networks; (iii) global activity in cortex may also shape regional distribution of neural activity in motor cortex. We demonstrate that these three psychomotor mechanisms and their underlying biochemical modulation are operative in both healthy subjects as well as in MDD, BD, and SCH subjects; the only difference consists in the fact that these mechanisms are abnormally balanced and thus manifest in extreme values in psychiatric disorders. We conclude that psychomotor mechanisms operate in a dimensional and cross-nosological way as their degrees of expression are related to levels of psychomotor activity (across different disorders) rather than to the diagnostic categories themselves. Psychomotor mechanisms and their biochemical modulation can be considered paradigmatic examples of a dimensional approach as suggested in RDoC and the recently introduced spatiotemporal psychopathology.
Published online: 17 June 2020
Gesehen am 07.05.2021